Evaluation of 6-Month Versus Continuous Isoniazid Preventive Therapy for Mycobacterium tuberculosis in Adults Living With HIV/AIDS in Malawi. (15th December 2020) - Hsieh, Yuli L.; Jahn, Andreas; Menzies, Nicolas A.; Yaesoubi, Reza; Salomon, Joshua A.; Girma, Belaineh; Gunde, Laurence; Eaton, Jeffrey W.; Auld, Andrew; Odo, Michael; Kiyiika, Caroline N.; Kalua, Thokozani; et al.
Abstract : Background: To assist the Malawi Ministry of Health to evaluate 2 competing strategies for scale-up of isoniazid preventive therapy (IPT) among HIV-positive adults receiving antiretroviral therapy. Setting: Malawi. Methods: We used a multidistrict, compartmental model of the Malawi tuberculosis (TB)/HIV epidemic to compare the anticipated health impacts of 6-month versus continuous IPT programs over a 12-year horizon while respecting a US10.8 million constraint on drug costs in the first 3 years. Results: The 6-month IPT program could be implemented nationwide, whereas the continuous IPT alternative could be introduced in 14 (of the 27) districts. By the end of year 12, the continuous IPT strategy was predicted to avert more TB cases than the 6-month alternative, although not statistically significant (2368 additional cases averted; 95% projection interval [PI], −1459 to 5023). The 6-month strategy required fewer person-years of IPT to avert a case of TB or death than the continuous strategy. For both programs, the mean reductions in TB incidence among people living with HIV by year 12 were expected to be <10%, and the cumulative numbers of IPT-related hepatotoxicity to exceed the number of all-cause deaths averted in the first 3 years. Conclusions: With the given budgetary constraint, the nationwide implementation of 6-month IPT would be more efficient and yield comparable health benefits than implementing a continuous IPT program in fewer districts. The anticipated health effects associated with both IPT strategies suggested that a combination of different TB intervention strategies would likely be required to yield a greater impact on TB control in settings such as Malawi, where antiretroviral therapycoverage is relatively high. Abstract : Supplemental Digital Content is Available in the Text.